Spatial Patterns of a Lethal White Syndrome Outbreak in Pseudodiploria strigosa - Guzmán-Urieta, Edgar O.; Jordán-Dahlgren, Eric (Frontiers in Marine Science, 2021)
We analyzed the spatial distribution patterns of a white syndrome (WS) outbreak affecting Pseudodiploria strigosa colonies in the northern Mexican Caribbean during 2018–2019. The purpose of the study was to describe the outbreak progression in a single species and determine if this WS incidence is related to the nearest diseased neighbor distance. Two separated sites with different P. strigosa colonial densities (Bocana: 0.08 col/m2; Picudas: 0.2 col/m2) were selected in similar habitats of the same reef complex. P. strigosa colonies within the survey sites were mapped, and their status was recorded (healthy, diseased, or dead) in sequential surveys until colonies died or the study terminated (306 days). Spatial distribution modes were assessed using Ripley’s K function. The spatial colony distribution was random in one site (Bocana) and clustered in the other (Picudas). However, the WS disease incidence per survey was randomly distributed in both sites throughout the observation period of the outbreak, suggesting that WS transmission at small spatial scales was independent of the colony distribution pattern and from the nearest diseased colonies. Survival probability since WS onset in surveyed colonies was different: 0% at Bocana and 14% at Picudas by April 2019. But, eventually, all diseased colonies died in both sites. WS outbreak timing was different at the two sites: Initial prevalence 8% at the Bocana site vs. 44% at Picudas site. Distribution of time to disease onset shown multimodality, with modes varying from 17 to 184 days and wide main modes amplitude suggest a highly variable resistance to the WS. Disease incidence was not abated during winter surveys. Differences between sites in the WS disease outbreak distribution and progression suggest that colony condition, environmental quality, and perhaps several transmission events played an essential role in the complex outbreak dynamics at the local spatial scale of our study.